Photoshop, this is your life!. - Biedny, David (Mac life)
Photoshop is everywhere. And while fundamentally it is the standard professional-quality image editor, it's also a cultural touchstone with a reach that extends to advertising, fashion magazines, television, film and news. Lighter version like Photoshop Elements, Photoshop.com, and even Photoshop Mobile on the iPhone have distilled its power for the masses, and sites like PhoshopDisasters.blogspot.com chronicle painful misuses for everyone to point at and giggle about. "Photoshop" the verb was even added to Webster's dictionary in 1992. In such a Photoshop-saturated society, it's easy to forget that the software hasn't been around forever.Since February 2010 marks the 20th anniversary of Photoshop 1.0, now is the perfect time to revisit everything from Adobe's systematic dismantling of its competition to the way the software was used to make Katie Couric "lose weight."